Heritage Building of Residensi Tunku Abdul Rahman: Preserve and Conserve for The Future - Noor Aisyah Mokhtar; Adi Irfan Che Ani; Suhana Johar; Nur Athirah Khalit; Afifuddin Husairi Mat Jusoh Hussain; Nor Zalina Harun; Mohd Fadhli Shah Khaidzir; Amira Shazlin Adnan (E3S Web of Conferences)
Residensi Tunku Abdul Rahman is over 100 years and registered as National Heritage. Heritage building sets certain standard in preserving their value where weather and climate change have become biggest challenge in maintaining the status. Humidity, hot and rainy weather, also sunlight in tropical region made some damages to the building. Therefore, preserving and conserving the building is important to give knowledge and create awareness to the public. This research made to inspect the damage and defects of the building, then, propose the scope of conservation work and building conservation. Analysis of damage/defects thorough the building using the Building Condition Assessment Rating System (BCARS) by identifying the level of building condition and its’ rating. The basis of the assessment is in the aspects of safety, functionality, and maintainability of the building that was assisted by several equipment used for the purpose of damage assessment and measuring work. Based on the analysis, there are 71 types of damage that were identified including rotten and broken wood louvres and wall surfaces with a total of 15 damage each and a percentage of 7.5% each. Taking care of heritage building from climate and weather change needs constant preservation and maintenance.